Substance Use and HIV among Subjects Attending Integrated Counseling and Testing Centre in South India: A Case Control Study - NR Ramesh Masthi; MS Phaneendra; Pradeep Banandur; Pruthvi S (Medsci Publications, 2019)
Introduction: There is limited understanding of the association be- tween various forms of substance use (non-injectable forms name- ly chewable tobacco, smoking and alcohol) and HIV. This study was conducted to assess the association between tobacco chewing, smoking, alcohol, other non-injectable substances and HIV status. Methods: This was a case control study done among attendees in the Integrated Counseling and Testing Centre (ICTC) of a medical college hospital situated in Bengaluru. Eligible subjects were inter- viewed using pre-tested, semi-structured proforma prior to testing for HIV status. Information on substance use was collected using Modified Fagerstrom questionnaire for smokeless tobacco, CAGE questionnaire for alcohol, CAGE questionnaire for nicotine de- pendence and WHO - ASSIST V3.0 for other non-injectable sub- stances. Result: Age group of 26-35 years (AOR = 3.70, 95% CI : 1.02 - 13.34), those who were married (AOR = 4.01, 95% CI : 1.31 - 12.28), separated (AOR = 17.45, 95% CI : 3.07 - 98.96), those referred by a doctor (AOR = 5.15, 95% CI : 2.03 - 13.10), chewable tobacco users (AOR = 11.28, 95% CI : 1.25 - 101.64) and alcohol dependents (AOR = 7.41, 95% CI : 2.02 - 27.25) were found to be at risk for acquiring HIV. Conclusion: Smokeless tobacco use and alcohol dependence was associated with HIV positivity.